Tattoo : Bilder die unter die Haut gehen. - Ermacora, Beate; Oettermann, Stephan; Riese, Ute; Schmidt, Hans-Werner; Kunsthalle zu Kiel; Christian-Albrechts-Universität, Kiel (Kiel : Kunsthalle zu Kiel, 1996)
Acconci, Vito ; Bair, Jamey ; Baldessari, John ; Carson, Karen ; Deleporte, Anne ; Diamond, Jessica ; Dietman, Erik ; Flatz ; Gonzalez-Foerster, Dominique ; Gotscho ; Grant, Peter ; Grünfeld, Thomas ; Joisten, Bernard ; Joseph, Pierre ; Mason, Thomas Kelly ; Kilimnik, Karen ; Knechtel, Tom ; Larner, Liz ; lee, Richard ; Levine, Les ; Lindell, John ; Luche, Ingrid ; Magnin, Stéphane ; Mayaux, Philippe ; Meyer, Daniel ; Mittleman, Paul ; Moreno, David ; Morgana, Aimée ; Nagy, Peter ; Hanson, Steve ; Pardo, Jorge ; Paris, Guillaume ; Parreno, Philippe ; Scher, Julia ; Steiner, Stéphane ; Turk, Gavin ; Bernard, Sarah V. ; Vilmouth, Jean-Luc ; Wurtz ; Weiner, Lawrence
bibliog. p. 45
Duits
Tattoo : Bilder die unter die Haut gehen, Kunsthalle zu Kiel, 23. Juni bis 25. August 1996
boek